Pengaruh Insentif, Target Penjualan, dan Kepuasan Kerja Terhadap Kinerja Karyawan Frontliner PT. Accentuates - Sugeng Riyadi; Farid Al Rizky (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to investigate and demonstrate if work happiness, sales objectives, and incentives affect frontline staff' performance. PT. Highlights. This research technique combines an explanatory research approach with quantitative research tools. Questionnaires and secondary data were the methods utilized to acquire the data. Multiple regression is used in the data analysis process with the use of SPSS software. The multiple regression test findings indicate that the incentive variable b1 = 0.393: the employee performance incentive variable's regression coefficient value will be higher, demonstrating that incentives have a considerable impact on frontline workers' performance. It is established that sales objectives have a major impact on frontline workers' performance, as shown by PT. Accentutaes, in the sales target variable b2 = 0.357, where the regression coefficient value of the sales target variable employees will also improve. PT. Highlights. Additionally, the job happiness variable's regression coefficient value, b3 = 0.397, will also increase, demonstrating the substantial impact that work contentment has on frontline employees' performance. PT. Highlights. With a computed t value of 5.998, a t table value of 1.979, and a significance value of 0.000 < 0.05, the incentive variable (X1) significantly affects frontline staff performance. PT. Highlights. With a computed t value of 4.710, a t table value of 1.979, and a significance value of 0.000 < 0.05, the sales goal variable (X2) significantly affects frontline staff performance. PT. Highlights. With a computed t value of 6.390, a t table value of 1.980, and a significance value of 0.000 <0.05, the work satisfaction variable (X1) significantly affects frontline employees' performance, according to PT. Accentuates.